A design of nonprime block irregular LDPC codes via CRT - Chusin, Chalit; Prasartkaew, Chutima; Timakul, Sekson; Choomchuay, Somsak (My University, 2010)
This paper presents a new design of irregular LDPC codes that supports arbitrary block length. We propose the efficient construction method when nonprime size sub-matrices are used. The problem where GCD(L1,L 2) that left unsolved has been tackled. We also consider the case GCD(L1,L2)=1 but L1 or L2 is a nonprime number. The results show that our designed codes have superior performance compared to MAC. The resulted codes still hold the attractive properties of LDPC codes. The performances of interleaved codes are higher than noninterleaved codes and it goes higher as SNR is increased. ©2010 IEEE.
Keywords: CRT; Interleave; Irregular; LDPC codes; Nonprime